Metal ion cages with stabilized conformations : synthesis, characterization and properties - Naidoo, Kevin Jonathan (Department of Chemistry, 2016)
The stabilized conformers lel₃, lel₂ob, ob₂lel and ob₃ of the [Co(±pn)₃]³⁺ system have previously been synthesized giving relative equilibrium (100 °C) amounts of 35.0 : 41.1 : 18.0 : 4.0. With the recent encapsulation of the resolved lel₃-[Co(pn)₃₋]Cl₃ complexes, and their subsequent interconversion to the ob₃-[Co(NH₃)₂-pnsar]Cl₅ diastereomers, the synthesis of the lel₂ob and ob₂lel cage complexes is a necessity to complete the investigation of the [Co(NH₃)₂-pnsar]⁵⁺ system. Consequently the eight Δ, Λ isomers of the lel₂ob-[Co(NH₃)₂-pnsar]Cl₅ complex were synthesised in a one pot reaction and resolved into the respective isomers having the following relative yields: lel₂ob-1 (~ 24% ), lel₂ob-2 ( ~ 43% ), lel₂ob-3 ( ~ 28%) and lel₂ob-4 (~ 5%). The resolution order of these isomers on SP Sephadex C-25 was used to tentatively identify the (3 mer and 1 fac) geometrical isomers of these lel₂ob diastereomers. For the first time ob character was directly encapsulated with the synthesis of the ob₂lel-[Co(NH₃)₂-pnsar]Cl₅ conformers ( ~ 1 % ). NMR analysis showed these to consist almost entirely (80%) of the ob₂lel-1 isomer. The geometry of this isomer was later discovered to be most favourable when the lel₂ob-1 isomer gave a 50% conversion to the ob₂lel-1 isomer, unlike the poor conversions of the ob₂lel-2 (~ 5%) and the ob₂lel-3 (~ 15%). The electronic spectra (UV /VIS and CD) of the individual isomers were investigated and revealed the presence of large distortion of the CoN₆ chromophore from regular Oh geometry. This was confirmed by the crystal structural analysis of the lel₂ob-2 isomer which reveal a trigonal twist angle (ф) of ~ 45°. The crystal structure also proved the identification logic right, which was based on the relation between chemical and resolution order evidence. The infrared spectra of [Co(NH₃)₂-sar]⁵⁺ ion was analysed using isotopic labelling methods in combination with the results of group theory calculations. These assignments make it possible to study the spectra of the [Co(NH₃)₂-pnsar]⁵⁺ isomeric complexes. Comparison of the infrared spectra of these complexes reflect the increase in number of bands on progressing from D₃, through C₃ to C₁ symmetry. Even the orientation of methyl groups in the different conformer types affect the symmetry of the CoN₆ core.